2018
DOI: 10.1038/s41591-018-0071-1
|View full text |Cite
|
Sign up to set email alerts
|

Poly(GR) impairs protein translation and stress granule dynamics in C9orf72-associated frontotemporal dementia and amyotrophic lateral sclerosis

Abstract: The major genetic cause of frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) is a C9orf72 GC repeat expansion. Proposed mechanisms by which the expansion causes c9FTD/ALS include toxicity from repeat-containing RNA and from dipeptide repeat proteins translated from these transcripts. To investigate the contribution of poly(GR) dipeptide repeat proteins to c9FTD/ALS pathogenesis in a mammalian in vivo model, we generated mice that expressed GFP-(GR) in the brain. GFP-(GR) mice developed age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
293
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(319 citation statements)
references
References 45 publications
24
293
2
Order By: Relevance
“…As positive controls, transfection of polyGA, polyPG, and polyGR cloned downstream of canonical ATG start codons embedded in consensus Kozak sequences (gccATGg) resulted in higher DPR protein expression (Figs EV1C and EV2C) and consequently in higher neuronal cell toxicities, especially for polyGR ( Fig 3A). These results are similar to the toxicity reported for DPR proteins driven by artificial ATG start codons and where polyGR are more toxic than polyGA or polyGP (May et al, 2014;Mizielinska et al, 2014;Yamakawa et al, 2015;Lopez-Gonzalez et al, 2016Schludi et al, 2017;Zhang et al, 2018;Choi et al, 2019). DPR proteins form protein aggregates that are degraded by autophagy (Cristofani et al, 2018).…”
Section: Decreased Expression Of C9orf72 Synergizes Dpr Protein Toxicitysupporting
confidence: 86%
See 1 more Smart Citation
“…As positive controls, transfection of polyGA, polyPG, and polyGR cloned downstream of canonical ATG start codons embedded in consensus Kozak sequences (gccATGg) resulted in higher DPR protein expression (Figs EV1C and EV2C) and consequently in higher neuronal cell toxicities, especially for polyGR ( Fig 3A). These results are similar to the toxicity reported for DPR proteins driven by artificial ATG start codons and where polyGR are more toxic than polyGA or polyGP (May et al, 2014;Mizielinska et al, 2014;Yamakawa et al, 2015;Lopez-Gonzalez et al, 2016Schludi et al, 2017;Zhang et al, 2018;Choi et al, 2019). DPR proteins form protein aggregates that are degraded by autophagy (Cristofani et al, 2018).…”
Section: Decreased Expression Of C9orf72 Synergizes Dpr Protein Toxicitysupporting
confidence: 86%
“…Indeed, we found that DPR proteins expressed under their natural sequences caused only limited toxicity, which is consistent with their limited expression. Mutation of their near‐cognate codons into AUG canonical start codons enhanced both DPR protein expression and toxicity, especially for the polyGR DPR protein, as consistently reported in various recent studies (Lopez‐Gonzalez et al , , ; Zhang et al , ; Choi et al , ). Conversely, deletions of these DPR initiation codons abolished neuronal cell death, suggesting that expanded repeats cause little toxicity at the RNA level and that RAN translation initiating within the repeats is not sufficiently efficient to drive toxicity, at least with the limited number of repeats used in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…GA expression resulted in a small increase in insoluble phosphorylated TDP-43 in one study [92], and rare inclusions in another [93]. The expression of GFP-(GR) 100 using adenovirus-mediated delivery into neonatal mouse brain results in motor deficits and a progressive reduction in associative memory, associated with rare TDP-43 but no poly(GR) inclusions [95]. Surprisingly, although there is evidence for the association of poly(GR) with nucleolar stress, nucleocytoplasmic transport dysfunction and nuclear membrane integrity in cell models and patient tissue [86,[96][97][98][99], no evidence for these pathways was observed in this study.…”
Section: C9orf72mentioning
confidence: 97%
“…Most neuronal DPR aggregates occur as compact round or stellate cytoplasmic inclusions. Diffusely DPR-stained neurons are rare, ~4% of poly-GR positive cells in one study (frontal cortex); these authors speculated, based on in vitro data, that diffuse DPR staining represents a transitional state preceding compact inclusion formation [172]. …”
Section: Clinical and Anatomical Features Of C9orf72-ftd/alsmentioning
confidence: 99%
“…Like RNA foci, poly-GA inclusions co-localize with, and may sequester, various proteins including Drosha, Unc119, and HR23B in neurons, often leading to protein mislocalization [88, 110, 124, 173]. Moreover, diffuse and aggregated cytoplasmic poly-GR was shown to colocalize with ribosomal proteins S6 and L21 and translation initiation factor eIF3η in frontal cortex from 3 patients with C9orf72 -FTD/ALS [172]. A similar study also reported that poly-GR, and to a lesser extent poly-PR, co-aggregate with STAU2 and several ribosomal proteins including S6, S25, L19, and L36A [54].…”
Section: Clinical and Anatomical Features Of C9orf72-ftd/alsmentioning
confidence: 99%